Comparative study on the antibacterial activities of neem oil, mustard oil and black seed oil against staphylococcus aureus, klebsiella pneumoniae, bacillus cereus, salmonella typhi and pseudomonas aeruginosa - Shova, Nishat Anzum (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.